INFLUENCE OF PRICES OF GOODS ANDA PROMOTIONAL MEDIA FOR E-COMMERCE SALES PLANNING SYSTEMS - Arman Syah Putra; Hielvita Ludiya; Nurul Aisyah; Budhi Sriyono Prasetyo (Bajang Institute, 2021)
The background of this study is to find out the variables that affect the sales system with e-commerce media, by knowing the influencing variables will be able to correct deficiencies in the existing sales system, and can increase the sale of a product or service being marketed. The method chosen in this research is to use quantitative methods by using surveys to search for data in the field, this is done in order to obtain real and accountable data so that the data can be used as the basis for this research and future research. The problem raised is to find out whether there is a relationship between the variable price of goods on e-commerce and promotional media on e-commerce, with the existence of these two variables, data searches can be carried out so as to produce new research data. The results of this study will produce data that can answer the research problem raised, the results of his research there is a significant relationship of the price of goods to e-commerce and there is a significant relationship between the variables of promotional media on e-commerce.